Copolyimide film as well as preparation method and application thereof

The copolymerized polyimide film addresses the challenge of simultaneous high permeability and selectivity in gas separation membranes by adjusting ether oxygen group ratios, achieving superior gas separation performance and stability.

CN119215699APending Publication Date: 2024-12-31TIANJIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411484135.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing polyimide gas separation membranes face challenges in achieving high permeability and selectivity simultaneously, inhibiting long-term gas separation performance and membrane stability.

Method used

A copolymerized polyimide film is developed by adjusting the ratio of ether oxygen groups in the monomer composition, incorporating dianhydride monomers with and without ether oxygen groups, and using specific catalysts and solvents to regulate polymer chain structure and free volume, enhancing permeability and selectivity.

Benefits of technology

The copolymerized polyimide film achieves improved permeability and balanced selectivity, exceeding the Robeson upper limit in gas separation performance, particularly in separating H2, O2, CO2, and CH4 mixtures, with enhanced thermal stability and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215699A_ABST
    Figure CN119215699A_ABST
Patent Text Reader

Abstract

The invention provides a copolyimide film as well as a preparation method and application thereof, and belongs to the technical field of polymeric membrane separation. The copolyimide film has a structure as shown in a formula I or a formula II: # imgabs 0 # formula I and # imgabs 1 # formula II, both the formula I and the formula II comprise a part which has a polymerization degree of m and contains an ether oxygen group-loaded dianhydride monomer and a part which has a polymerization degree of n and contains an ether oxygen group-unloaded dianhydride monomer. The obtained copolyimide film is mainly used for gas separation. According to the monomers containing ether oxygen groups among biphenyl units, by adjusting the proper proportion of the part containing the dianhydride monomer loaded with the ether oxygen groups to the part containing the dianhydride monomer unloaded with the ether oxygen groups, the rotary motion among benzene rings is limited, the rigidity and free volume of a polymer chain are improved, and the polymer has higher permeability; and meanwhile, selectivity can be balanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer membrane separation, and in particular relates to a copolymerized polyimide (COPI) film and a preparation method and application thereof. Background Art

[0002] At present, gas separation technology is of great significance for meeting the needs of human society for different gases and promoting the development of various industrial fields. For example, oxygen is used for respiratory support and oxygen supply therapy in the medical industry; hydrogen is used for fuel cells and hydrogen energy, etc. In addition, the generation of mixed gases is a common phenomenon in various industrial processes. For example, in the petrochemical industry, the gas mixture produced by the crude oil processing process contains multiple components, such as methane, ethylene and propane. At this time, the gas separation technology can effectively separate the various components in the mixed gas, thereby realizing the effective utilization of resources.

[0003] As a gas separation membrane material, polyimide has the advantages of high thermal stability, high mechanical properties, good film-forming properties, and tolerance to different solvents. Its huge application prospects have been fully recognized. In recent years, many countries have listed the development and utilization of polyimide as the most promising research project in the 21st century. Polyimide is mainly a class of high-performance polymers containing imide rings generated by the polycondensation reaction of diamine and dianhydride monomers. However, the long-standing problems of not being able to simultaneously obtain high permeability and high selectivity have inhibited long-term gas separation performance and membrane stability. Therefore, the development of gas separation membranes with high permeability and high selectivity is urgent for membrane-based gas separation research. Summary of the invention

[0004] The invention provides a copolymer polyimide (COPI) film and a preparation method thereof, and the gas separation performance of the film is regulated by changing the ratio of ether oxygen groups in the monomer.

[0005] The present invention provides a copolymerized polyimide film having a structure as shown in Formula I or Formula II:

[0006] Formula I and Formula II both include a portion of dianhydride monomers containing ether oxygen groups with a polymerization degree of m and a portion of dianhydride monomers containing no ether oxygen groups with a polymerization degree of n; Where m:n is (1-100):(0-100), and 10 <m+n<1000; X is independently selected from: , , , , , , ; Ar is independently selected from:

[0007] Further, m:n is 100:0, 75:25, 50:50, 25:75; Preferably, m:n is 50:50.

[0008] Further, X is independently selected from: .

[0009] The present invention also provides a method for preparing a copolymerized polyimide film, comprising the following steps: S1. Under a protective atmosphere, add o-hydroxydiamine and solvent to a polymerization tube, mix, add dianhydride monomers carrying ether oxygen groups, dianhydride monomers not carrying ether oxygen groups, and a catalyst, heat to a temperature of 150-180° C. to react, and obtain a viscous reaction solution; S2, treating the viscous reaction solution by solvent precipitation method, drying, and obtaining copolymerized polyimide; S3, dissolving the copolymerized polyimide in a volatile solvent, adding the resulting solution into a culture dish, and evaporating the solvent to obtain a copolymerized polyimide film; wherein, The o-hydroxydiamine has a structure as shown in the following formula: or ; The dianhydride monomer carrying the ether oxygen group has a structure as shown in the following formula: ; X is independently selected from: , , , , , , ; The dianhydride monomer without an ether oxygen group has a structure as shown in the following formula: ; Ar is independently selected from:

[0010] Furthermore, in step S1, the ratio of the total amount of dianhydride monomers, o-hydroxydiamine, and catalyst is 2 mmol:2 mmol:(0.1-2) mL; wherein the total amount of dianhydride monomers is the total molar number of dianhydride monomers loaded with ether oxygen groups and dianhydride monomers not loaded with ether oxygen groups.

[0011] Further, in step S1, the catalyst is selected from a basic catalyst and an acidic catalyst; Preferably, the alkaline catalyst comprises at least one of isoquinoline and triethylamine; Preferably, the acidic catalyst includes at least one of benzoic acid and acetic anhydride. Furthermore, in step S1, the solvent includes at least one of m-cresol, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, 1,4-dioxane, and chloroform; In step S3, the volatile solvent includes at least one of tetrahydrofuran, 1,4-dioxane, chloroform and dichloromethane.

[0012] Furthermore, in step S2, the viscous reaction liquid is treated by a solvent precipitation method, specifically, the obtained viscous reaction liquid is poured into a mixed solution of ethanol and water, and precipitated after standing; Preferably, in the mixed solution of ethanol and water, the volume ratio of ethanol to water is 1:1; In step S2, the drying is specifically performed at 80-120° C. for 1-2 days in a vacuum oven. The present invention also proposes the use of the copolymerized polyimide film and the copolymerized polyimide film prepared by the preparation method in gas separation.

[0013] Furthermore, the application includes: using copolymerized polyimide film to separate H2 from H2 / N2 mixed gas, separate O2 from O2 / N2 mixed gas, separate CO2 from CO2 / CH4 mixed gas, separate H2 from H2 / CH4 mixed gas or separate CO2 from CO2 / N2 mixed gas.

[0014] The present invention has the following advantages: The copolymerized polyimide (COPI) film proposed in the present invention contains monomers with ether oxygen groups between biphenyl units. By adjusting the appropriate ratio of the part containing the dianhydride monomer with loaded ether oxygen groups and the part containing the dianhydride monomer without loaded ether oxygen groups, the rotational movement between the benzene rings is restricted, the rigidity and free volume of the polymer chain are improved, the polymer has higher permeability, and the selectivity can be balanced at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0016] Figure 11 is the H-NMR spectra of the COPI films obtained in Examples 1-4 and Comparative Example 1 of the present invention; Figure 2 is the infrared spectra of the COPI films obtained in Examples 1-4 and Comparative Example 1 of the present invention; Figure 3 a) Thermogravimetric analysis (TGA) result graph, b) differential scanning calorimetry (DSC) result graph, c) differential thermogravimetric analysis (DTG) result graph, d) double y-axis graph of 5% and 10% mass loss corresponding temperature and maximum thermal decomposition rate corresponding temperature of COPI films obtained in Examples 1-4 of the present invention and Comparative Example 1; Figure 4 Graph showing the pure gas separation performance of the COPI membranes obtained in Examples 1-4 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0018] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings.

[0019] On the one hand, an embodiment of the present invention provides a copolymer polyimide (COPI) film having a structure as shown in Formula I or Formula II:

[0020] Formula I and Formula II both include a portion of dianhydride monomers containing ether oxygen groups with a polymerization degree of m and a portion of dianhydride monomers containing no ether oxygen groups with a polymerization degree of n; Where m:n is (1-100):(0-100), and 10 <m+n<1000; X is independently selected from: , , , , , , ; Ar is independently selected from:

[0021] It should be noted that Ar is independently selected from the structure and the dotted lines represent the bond positions.

[0022] The copolymerized polyimide (COPI) film proposed in the embodiment of the present invention contains monomers with ether oxygen groups between biphenyl units. By adjusting the appropriate ratio of the part containing the dianhydride monomer with loaded ether oxygen groups and the part containing the dianhydride monomer without loaded ether oxygen groups, the rotational movement between the benzene rings is restricted, the rigidity and free volume of the polymer chain are improved, and the polymer has higher permeability while being able to balance the selectivity.

[0023] In a preferred embodiment of the present invention, m:n can be 100:0, 90:10, 80:20, 75:25, 70:30, 60:40, 50:50, 40:60, 30:70, 25:75, 20:80 or 10:90, etc. Preferably, m:n can be 100:0, 75:25, 50:50 or 25:75. More preferably, m:n is 50:50. In the embodiment of the present invention, when m:n is 50:50, the CO2 / CH4 and H2 / CO2 separation performance of the gas separation membrane reaches the Robeson upper limit in 2008 [SWAIDAN R, GHANEM B, PINNAU I. Fine-Tuned Intrinsically Ultramicroporous Polymers Redefine the Permeability / Selectivity Upper Bounds of Membrane-Based Air and Hydrogen Separations[J]. ACS MacroLetters, 2015: 947-951]. It has indispensable application value in the fields of H2 purification in methanol reforming process, CO2 capture in zero-emission fossil fuel power generation process, and H2 recovery in ammonia production.

[0024] In a preferred embodiment of the present invention, X is independently selected from: . In the embodiments of the present invention, in the part of the dianhydride monomer containing the ether oxygen group with a degree of polymerization of m, the presence of fluorine generally reduces the thermal expansion coefficient and provides increased solubility. At the same time, a series of copolymerized polyimides with non-coplanar biphenyl structural units as the main unit and bulky side chain substituents (-CF3) as the auxiliary rigid chain are used as separation layers. These large groups will effectively inhibit chain filling, and the non-coplanar conformation of the biphenyl structure will also reduce the dense stacking of the polymer main chain, thereby increasing the free volume while allowing the polymer to have more cavity size to obtain a higher permeation flux.

[0025] The embodiment of the present invention also provides a method for preparing a copolymerized polyimide (COPI) film, comprising the following steps: S1. Under a protective atmosphere, add o-hydroxydiamine and solvent to a polymerization tube, mix, add dianhydride monomers carrying ether oxygen groups, dianhydride monomers not carrying ether oxygen groups, and a catalyst, heat to a temperature of 150-180° C. to react, and obtain a viscous reaction solution; S2, treating the viscous reaction solution by solvent precipitation method, drying, and obtaining copolymerized polyimide; S3, dissolving the copolymerized polyimide in a volatile solvent, adding the resulting solution into a culture dish, and evaporating the solvent to obtain a copolymerized polyimide film; wherein, The o-hydroxydiamine has a structure as shown in the following formula: or ; The dianhydride monomer carrying the ether oxygen group has a structure as shown in the following formula: ; X is independently selected from: , , , , , , ; The dianhydride monomer without an ether oxygen group has a structure as shown in the following formula: ; Ar is independently selected from:

[0026] In the embodiment of the present invention, the copolymerized polyimide film is obtained by copolymerizing three monomers in a certain ratio, including a dianhydride monomer carrying an ether oxygen group, a dianhydride monomer not carrying an ether oxygen group, and an o-hydroxy diamine monomer (SBI-NH2 or 6FAP (2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane)). As shown in the following reaction example (taking SBI-NH2, 6FDA and 6CFDA as examples): ; Random copolymer COPI film (COPI-6FDA) was synthesized from 3,3,3',3'-tetramethyl-1,1'-spirobiindan-5,5'-diamino-6,6'-diol (SBI-NH2), 2,2'-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA) and 9,9-bis(trifluoromethyl)xanthenetetracarboxylic dianhydride (6CFDA) in a certain proportion in the presence of a catalyst and a solvent. The preparation method of the COPI film proposed in the embodiment of the present invention effectively adjusts the appropriate ratio of the part containing the dianhydride monomer loaded with ether oxygen group and the part containing the dianhydride monomer not loaded with ether oxygen group through copolymerization reaction, thereby regulating the chain spacing of the COPI film, balancing the permeability and selectivity, and obtaining a gas separation membrane with optimal gas separation performance. Specifically, in the embodiments of the present invention, a copolymerization method is used to embed bulky side chain substituent groups, and the ratio of ether oxygen groups loaded between biphenyl units in the polymer segment is adjusted, thereby achieving regulation of the polymer segment structure at the atomic level. This method can not only effectively change the rigid state of the polymer segment structure, but also regulate the segment stacking structure, provide the polymer free volume fraction, further improve its gas separation performance, and balance permeability and selectivity. In one embodiment of the present invention, in step S1, the ratio of the total amount of dianhydride monomers, o-hydroxydiamine, and catalyst is 2 mmol: 2 mmol: (0.1-2) mL; wherein the total amount of dianhydride monomers is the total molar number of dianhydride monomers loaded with ether oxygen groups and dianhydride monomers not loaded with ether oxygen groups.

[0027] In one embodiment of the present invention, in step S1, the solvent includes at least one of m-cresol, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, 1,4-dioxane, and chloroform.

[0028] In one embodiment of the present invention, in step S1, the catalyst is selected from a basic catalyst and an acidic catalyst.

[0029] Furthermore, in step S1, the alkaline catalyst includes at least one of isoquinoline and triethylamine. Furthermore, in step S1, the acidic catalyst includes at least one of benzoic acid and acetic anhydride. In the embodiment of the present invention, the catalyst is in a liquid state at room temperature and is directly added in a liquid state. The catalyst that is not in a liquid state at room temperature can be heated to a molten state before being added.

[0030] In one embodiment of the present invention, in step S1, a magnet is installed in the polymerization tube, and the rotation of the magnet forms stirring, thereby achieving mixing.

[0031] In one embodiment of the present invention, in step S1, the viscosity of the obtained reaction solution is 6000-20w cps.

[0032] Furthermore, in step S3, the volatile solvent includes at least one of tetrahydrofuran, 1,4-dioxane, chloroform and dichloromethane.

[0033] In one embodiment of the present invention, in step S1, the protective atmosphere includes at least one of nitrogen and argon.

[0034] In one embodiment of the present invention, in step S2, the viscous reaction liquid is treated by a solvent precipitation method, specifically, the obtained viscous reaction liquid is poured into a mixed solution of ethanol and water, and precipitated after standing. Further, the above operation is repeated three times so that the reaction product is fully precipitated. Wherein, in the mixed solution of ethanol and water, the volume ratio of ethanol to water is 1:1. In one embodiment of the present invention, in step S2, the drying is specifically performed at 80-120° C. for 1-2 days. The drying is performed in a vacuum oven. In one embodiment of the present invention, in step S3, the volatile solvent includes at least one of tetrahydrofuran, 1,4-dioxane, chloroform and dichloromethane.

[0035] In one embodiment of the present invention, in step S3, the solution is filtered into the culture dish through a filter. The filter is a polytetrafluoroethylene (PTFE) filter with a pore size of 0.45 μm.

[0036] In one embodiment of the present invention, step S3 further comprises drying the copolymerized polyimide film obtained by solvent volatilization in a vacuum oven at 80-120°C for 10-15 hours, and then heating it in a tube furnace under N2 atmosphere at 200-250°C for 1-5 hours. Preferably, the copolymerized polyimide film obtained by solvent volatilization is dried in a vacuum oven at 100°C for 12 hours, and then heated in a tube furnace under N2 atmosphere at 230°C for 2 hours. In this way, the remaining solvent is completely removed.

[0037] In one embodiment of the present invention, in step S3, the thickness of the obtained copolymerized polyimide film is 50-100 μm. The obtained copolymerized polyimide film is an isotropic film.

[0038] On the other hand, the embodiments of the present invention also provide the application of copolymerized polyimide film in gas separation.

[0039] In one embodiment of the present invention, the application includes: using a copolymer polyimide film to separate H2 from a H2 / N2 mixed gas, to separate O2 from an O2 / N2 mixed gas, to separate CO2 from a CO2 / CH4 mixed gas, or to separate at least one of H2 from a H2 / CH4 mixed gas or CO2 from a CO2 / N2 mixed gas.

[0040] The present invention will be described in detail below with reference to embodiments.

[0041] Example 1 A method for preparing a COPI film (the dianhydride monomer carrying an ether oxygen group is 6FCDA, and the dianhydride monomer not carrying an ether oxygen group is 6FDA, m:n=50:50), comprising the following steps: The structural formula of the COPI film (denoted as COPI-6FDA (50:50)) is as follows:

[0042] Under nitrogen atmosphere, 3,3,3',3'-tetramethyl-1,1'-spirobiindane-5,5'-diamino-6,6'-diol (SBI-NH2) (0.6770 g, 2 mmol) monomer was added to a polymerization tube equipped with a magnet, and then 6 mL of solvent m-cresol was added and stirring was started. 9, 9-bis(trifluoromethyl)-2, 3, 6, 7-oxanthene tetracarboxylic dianhydride (6FCDA) (0.4582 g, 1 mmol) and 2,2'-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride 6FDA (0.4442 g, 1 mmol) monomers were weighed, wherein the total molar number of the two dianhydride monomers was equal to the molar number of the SBI-NH2 monomer. 6FDA and 6FCDA were mixed and poured into the polymerization tube, and then the catalyst isoquinoline (0.2 mL); gradually heat the temperature to 170°C, and after sufficient dissolution, react until the magnet cannot rotate (viscosity is about 10w cps), to obtain a viscous reaction solution; The obtained viscous reaction solution was slowly poured into a mixed solution of ethanol and water (volume ratio 1:1), and precipitated after standing; after repeating three times, it was placed in a vacuum oven at 90 ° C and dried for 2 days to obtain a copolymerized polyimide polymer for film laying; The copolymerized polyimide polymer was dissolved in tetrahydrofuran (THF), stirred thoroughly to dissolve the solute, and then the solution was filtered through a 0.45 μm PTFE filter into a petri dish with a flat surface. After the solvent evaporated, an isotropic film was obtained. The solvent evaporated cleanly to obtain a transparent film with a thickness of 80 μm, which was dried in a vacuum oven at 100 °C for 12 h, and further heated in a tube furnace at 230 °C for 2 h under N2 atmosphere to ensure that the remaining solvent was completely removed to obtain a COPI film.

[0043] NMR structural characterization of COPI film: COPI-6FDA (50:50): 1 H NMR (400 MHz, DMSO) δ 9.62 (d, J = 13.9 Hz, 4H), 8.29 (s, 2H), 8.16 (d, J = 5.7 Hz, 2H), 8.07 (s, 2H), 7.98 (s, 1H), 7.78 (s, 2H), 7.18 (d, J = 8.6 Hz, 4H), 6.45 (d, J = 7.6 Hz, 4H), 2.43 – 2.01 (m, 9H), 1.59 – 1.15 (m, 28H). Performance test of COPI film: The pure gas permeation properties of the resulting films were measured by the constant volume / variable pressure method. In order to remove any contaminants in the permeation system and the membrane, the system with a masking membrane in a sealed permeation cell was degassed for 24 hours. The pure gas permeabilities of He, H2, N2, O2, CH4 and CO2 were measured at 2 bar and 35 °C. The gas permeabilities were determined as follows:

[0044] In the formula, the permeability coefficient P is expressed in barrer (1 barrer = 10 -10 cm 3 (STP)⋅cm cm -2 ⋅s -1 ⋅cm Hg -1 or 7.5 × 10 -18 m 3 (STP)⋅mm -2 ⋅s -1 ⋅Pa -1 ) as the unit; p up is the upstream pressure (cm Hg); T is the operating temperature (K); V d is the permeate volume (cm3); dp / dt is the permeate pressure change (cm Hg⋅s -1 ); A is the effective area of ​​the membrane (cm 2 ), l is the thickness (cm), R is the gas constant, which is equal to 0.278 cm 3 ⋅cm Hg cm -3 (STP)⋅K -1 . Pure gas selectivity α AB The calculation is as follows:

[0045] Among them, the permeability coefficients of gas A and gas B are denoted as P A , P B , D A , D B , S A , S B are the diffusion coefficients of A and B and the solubility coefficients of A and B, respectively. Each polymer membrane was tested three times, and the deviations of permeability and selectivity were within the range of ~5%. The specific results are as follows: The nitrogen permeability coefficient is 21.7 Barrer, the oxygen permeability coefficient is 107.2 Barrer, the methane permeability coefficient is 16.3 Barrer, the carbon dioxide permeability coefficient is 575.3 Barrer, and the hydrogen permeability coefficient is 672.2 Barrer; The selectivity coefficient of hydrogen / methane is 41.3, the selectivity coefficient of oxygen / nitrogen is 4.94, and the selectivity coefficient of carbon dioxide / methane is 35.3.

[0046] Example 2 A method for preparing a COPI film (the dianhydride monomer carrying an ether oxygen group is 6FCDA, and the dianhydride monomer not carrying an ether oxygen group is 6FDA, m:n=75:25), comprising the following steps: The structural formula of the COPI film (denoted as: COPI-6FDA (75:25)) is as follows:

[0047] Under nitrogen atmosphere, add SBI-NH2 (0.6770 g, 2 mmol) monomer to the polymerization tube equipped with a magnet, add 6 mL of solvent m-cresol, and start stirring; weigh 6FCDA (0.2291 g, 0.5 mmol) and 6FDA (0.6663 g, 1.5 mmol) monomers, where the total molar number of the two monomers is equal to that of the SBI monomer. Mix 6FDA and 6FCDA and pour them into the polymerization tube, add the catalyst isoquinoline (0.2 mL); gradually heat the temperature to 170 ° C, and react until the magnet cannot rotate after sufficient dissolution (viscosity is about 10w cps), and obtain a viscous reaction solution; The obtained viscous reaction solution was slowly poured into a mixed solution of ethanol and water (volume ratio 1:1), and precipitated after standing; after repeating three times, it was placed in a vacuum oven at 80 °C and dried for 2 days for film laying; The copolymerized polyimide polymer was dissolved in tetrahydrofuran (THF), stirred thoroughly to dissolve the solute, and then the solution was filtered through a 0.45 μm PTFE filter into a petri dish with a flat surface. After the solvent evaporated, an isotropic film was obtained. The solvent evaporated cleanly to obtain a transparent film with a thickness of 80 μm, which was dried in a vacuum oven at 100 °C for 12 h, and further heated in a tube furnace at 230 °C for 2 h under N2 atmosphere to ensure that the remaining solvent was completely removed to obtain a COPI film. NMR structural characterization of COPI film: COPI-6FDA (75:25): 1H NMR (400 MHz, DMSO) δ 8.29 (s, 2H), 8.16 (s, 1H), 2.20 (s, 1H), 1.35 (d, J = 22.2 Hz, 26H), 9.62 (d, J = 16.2 Hz, 4H), 8.07 (s,2H), 7.98 (s, 1H), 7.77 (s, 2H), 7.22 – 7.14 (m, 4H), 6.55 (q, J = 8.2 Hz,1H), 6.46 (s, 5H). Performance test of COPI film: The method is the same as in Example 1, and the specific results are as follows: COPI-6FDA (75:25) membrane gas separation test, nitrogen permeability coefficient is 20.2 Barrer, oxygen permeability coefficient is 96.85 Barrer, methane permeability coefficient is 16.9 Barrer, carbon dioxide permeability coefficient is 548.8 Barrer, hydrogen permeability coefficient is 581.1 Barrer; The selectivity coefficient of hydrogen / methane is 34.3, the selectivity coefficient of oxygen / nitrogen is 4.79, and the selectivity coefficient of carbon dioxide / methane is 32.4.

[0048] Example 3 A method for preparing a COPI film (the dianhydride monomer carrying an ether oxygen group is 6FCDA, and the dianhydride monomer not carrying an ether oxygen group is 6FDA, m:n=25:75), comprising the following steps: The structural formula of the COPI film (denoted as: COPI-6FDA (25:75)) is as follows:

[0049] Under nitrogen atmosphere, add an appropriate amount of SBI-NH2 (0.6770 g, 2 mmol) monomer to a polymerization tube equipped with a magnet, add 6 mL of solvent m-cresol, and start stirring. Weigh a certain amount of 6FCDA (0.6873 g, 1.5 mmol) and 6FDA (0.2221 g, 0.5 mmol) monomers, where the total molar number of the two monomers is equal to that of the SBI monomer. After 6FDA and 6FCDA are mixed and poured into the polymerization tube, add the catalyst isoquinoline (0.2 mL) and gradually heat the temperature to 170°C. After sufficient dissolution, react until the magnet cannot rotate (viscosity is about 10w cps), and a viscous reaction solution is obtained; The viscous reaction solution was slowly poured into a 1:1 ethanol-water solution and allowed to stand for precipitation. After three times, it was placed in a vacuum oven and dried at 100 °C for 1 day for film laying; The copolymerized polyimide polymer was dissolved in THF and stirred thoroughly to dissolve the solute. The solution was filtered through a 0.45 μm PTFE filter into a petri dish with a flat surface. After the solvent evaporated, an isotropic film was obtained. The solvent evaporated cleanly to obtain a transparent film with a thickness of 75 μm, which was dried in a vacuum oven at 100 °C for 12 h and further heated in a tube furnace at 230 °C for 2 h under N2 atmosphere to ensure that the remaining solvent was completely removed to obtain a COPI film.

[0050] NMR structural characterization of COPI film: COPI-6FDA (25:75): 1 H NMR (400 MHz, DMSO) δ 9.62 (d, J = 16.3 Hz, 4H), 8.29 (s, 2H), 8.16 (s, 1H), 8.07 (s, 2H), 7.98 (s, 1H), 7.77 (s, 2H), 7.22 –7.14 (m, 4H), 6.55 (q, J = 8.2 Hz, 1H), 6.46 (s, 5H), 2.20 (s, 1H), 1.35 (d,J = 22.3 Hz, 26H). Performance test of COPI film: The method is the same as in Example 1, and the specific results are as follows: COPI-6FDA (25:75) membrane gas separation test, nitrogen permeability coefficient is 8.0 Barrer, oxygen permeability coefficient is 46.7 Barrer, methane permeability coefficient is 4.9 Barrer, carbon dioxide permeability coefficient is 223.8 Barrer, hydrogen permeability coefficient is 563.9 Barrer; The selectivity coefficient of hydrogen / methane is 20.66, the selectivity coefficient of oxygen / nitrogen is 3.88, and the selectivity coefficient of carbon dioxide / methane is 26.84.

[0051] Example 4 A method for preparing a COPI film (the dianhydride monomer carrying an ether oxygen group is 6FCDA, m:n=100:0) comprises the following steps: The structural formula of COPI film (denoted as: COCPI) is as follows:

[0052] Under nitrogen atmosphere, 6FCDA (0.9146 g, 2 mmol) and SBI-NH2 (0.6770 g, 2 mmol) were added to a polymerization tube equipped with a magnetic particle in sequence, and 6 mL of m-cresol was added under argon atmosphere protection and stirring was started; the mixture was heated to 160°C and isoquinoline (0.4 mL) was added, and after sufficient dissolution, the mixture was reacted until the magnetic particle could not rotate (viscosity was about 10w cps), and a viscous reaction solution was obtained; The obtained viscous reaction liquid was slowly poured into a mixed solution of ethanol and water (volume ratio of 1:1), and precipitated after standing; after repeating three times, it was then dried in a vacuum oven at 120° C. for 24 hours to remove the residual solvent and obtain a COCPI powder polymer.

[0053] The polymer was dissolved in THF and stirred thoroughly to dissolve the solute; the solution was then filtered through a 0.45 μm PTFE filter into a flat petri dish, and an isotropic film was obtained after the solvent evaporated. The solvent evaporated cleanly to obtain a transparent film with a thickness of 78 μm, which was dried in a vacuum oven at 100 °C for 12 h and further heated in a tube furnace at 230 °C for 2 h under N2 atmosphere to ensure that the remaining solvent was completely removed to obtain a COPI film.

[0054] NMR structural characterization of COPI film: COCPI: 1 H NMR (400 MHz, DMSO) δ 9.65 (s, 2H), 8.29 (s, 2H), 8.08 (s,2H), 7.20 (s, 2H), 6.47 (s, 2H), 2.20 (s, 4H), 1.53 – 0.97 (m, 12H). Performance test of COPI film: The method is the same as in Example 1, and the specific results are as follows: COCPI membrane gas separation test, nitrogen permeability coefficient is 31.8 Barrer, oxygen permeability coefficient is 128.2 Barrer, methane permeability coefficient is 29.8 Barrer, carbon dioxide permeability coefficient is 763.5 Barrer, hydrogen permeability coefficient is 659.0 Barrer; The selectivity coefficients for hydrogen / methane are 21.1, oxygen / nitrogen are 4.03, and carbon dioxide / methane are 25.6.

[0055] Comparative Example 1 A method for preparing a COPI film (the dianhydride monomer without an ether oxygen group is 6FDA, m:n=0:100) comprises the following steps: Same as Example 4, except that 6FDA was used to replace 6FCDA, and the obtained film was recorded as CODPI.

[0056]

[0057] NMR structural characterization: CODPI: 1 H NMR (400 MHz, DMSO) δ 9.59 (s, 2H), 8.15 (d, J = 8.0 Hz,2H), 7.97 (s, 2H), 7.77 (s, 2H), 7.16 (s, 2H), 6.43 (s, 2H), 2.47 – 2.13 (m,4H), 1.33 (d, J = 20.7 Hz, 12H). Performance Test: The method is the same as in Example 1, and the specific results are as follows: CODPI membrane gas separation test, nitrogen permeability coefficient is 1.70 Barrer, oxygen permeability coefficient is 8.12 Barrer, methane permeability coefficient is 1.00 Barrer, carbon dioxide permeability coefficient is 40.12 Barrer, hydrogen permeability coefficient is 54.27 Barrer; The selectivity coefficient of hydrogen / methane is 54.27, the selectivity coefficient of oxygen / nitrogen is 4.78, and the selectivity coefficient of carbon dioxide / methane is 40.12.

[0058] The following is a result analysis, comparing the results obtained in the embodiment and the comparative example. Figure 1 The peaks in the hydrogen nuclear magnetic resonance spectra of the COPI films prepared in Examples 1-4 and Comparative Example 1 are Figure 1 It can be seen that the chemical shifts of H on the hydroxyl group of the copolymerized polyimide appear at 9.60 ppm and 9.65 ppm, respectively, and with the increase of the 6FCDA ratio, they first split into two peaks and then return to a single peak. The chemical shifts of H on the benzene ring groups of the two dianhydride units appear between 7.7-8.3 ppm; the characteristic peaks of aromatic protons in the diamine unit are located at 6.43-7.20 ppm.

[0059] Figure 2 The infrared spectra of the COPI films obtained in Examples 1-4 and Comparative Example 1 are shown in FIG. Figure 2 It can be found that the infrared spectrum has 1781, 1712, 1359-1373 and 719-744 cm -1 The absorption peaks of the imide ring are shown at 1781 and 1712 cm -1The characteristic infrared absorption peaks at 1359 and 1373 cm are the symmetric and asymmetric stretching vibrations of C=O (imide ring); -1 The infrared characteristic absorption peak at 719-744 cm is the stretching vibration of CN in imide; -1 The characteristic infrared absorption peaks at 1492 and 1425 cm -1 The characteristic infrared absorption peak at is the vibration peak of aromatic C=C.

[0060] Figure 3 a) Thermogravimetric analysis (TGA) results of the COPI films obtained in Examples 1-4 and Comparative Example 1, b) Differential scanning calorimetry (DSC) results, c) Derivative thermogravimetric analysis (DTG) results, and d) a double y-axis graph of the temperatures corresponding to 5% and 10% mass loss and the temperatures corresponding to the maximum thermal decomposition rate. Figure 3 It can be seen that the temperatures corresponding to 5% weight loss and 10% weight loss are the same for all COPI-6FDA films. Within a similar thermal stability range, the decomposition temperature and glass transition temperature gradually increase with the increase of 6FDA ratio.

[0061] Figure 4 The performance changes of the polymers obtained by controlling the ratio of ether oxygen units in Examples 1-4 and Comparative Example 1 are shown in Table 1. a), b), and c) are the selectivity and permeability of polymer membranes with different ratios of ether oxygen units. Figure 4 It can be obtained that by introducing ether oxygen groups between benzene rings, the interchain distance of polymer molecular segments is effectively increased, the dense stacking between segments is reduced, and the free volume of the polymer is increased, so that the polymer has more cavity size to obtain a higher permeation flux. With the continuous increase of the proportion of ether oxygen groups, the polymer permeability shows an upward trend and the selectivity decreases. The permeability coefficients of H2 and CO2 increase from 54.27 Barrer and 40.12 Barrer to 659.0 Barre and 763.5 Barrer, respectively, and the selectivity coefficient of hydrogen / methane decreases from 54.27 to 21.1. This confirms that the method of regulating the structure of copolymerized polyimide (COPI) film based on the proportion of ether oxygen groups and the gas separation application of the present invention are effective.

[0062] The copolymerized polyimide obtained by the present invention exhibits effective pure gas and gas mixture permeation performance. The permeability of pure gas CO2 obtained at 35°C and a feed pressure of about 30 psig ranges from about 40 Barrer to 763.5 Barrer, and the CO2 / CH4 selectivity is as high as about 40. This performance is much higher than that obtained in many current commercial membranes. In addition, the CO2 / CH4 and H2 / CH4 selectivities of the copolymerized polyimide will not decrease to almost the same extent as the reported CA and other commercial membranes, and this stability at moderate pressure is outstanding.

[0063] Example 5 A method for preparing a COPI film (the dianhydride monomer carrying an ether oxygen group is 6FCDA, the dianhydride monomer not carrying an ether oxygen group is 6FDA, m:n=1:1, and the diamine part is 6FAP monomer), comprising the following steps: The reaction formula of COPI film (denoted as: COAPI-6FDA (1:1)) is as follows:

[0064] Under nitrogen atmosphere, add 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) (0.7326 g, 2 mmol) monomer to a polymerization tube equipped with a magnet, add 6 mL of m-cresol, and start stirring. Weigh 6FCDA (0.4582 g, 1 mmol) and 6FDA (0.4442 g, 1 mmol) monomers, where the total molar number of the two monomers is equal to that of the 6FAP monomer. Mix 6FDA and 6FCDA and pour them into the polymerization tube, add isoquinoline (0.2 mL), and gradually heat the temperature to 170°C. After sufficient dissolution, react until the magnet cannot rotate (viscosity is about 10w cps), and a viscous reaction solution is obtained; The obtained solution was slowly poured into a mixed solution of ethanol and water (volume ratio 1:1), and precipitated after standing. After repeating three times, it was placed in a vacuum oven at 90 °C and dried for 2 days to obtain a copolymerized polyimide polymer for film laying; The copolymerized polyimide polymer was dissolved in THF, stirred thoroughly to dissolve the solute, and then the solution was filtered through a 0.45 μm PTFE filter into a petri dish with a flat surface. After the solvent evaporated, an isotropic film was obtained. The solvent evaporated cleanly to obtain a transparent film with a thickness of 85 μm, which was dried in a vacuum oven at 100 °C for 12 h and further heated in a tube furnace at 230 °C for 2 h under N2 atmosphere to ensure that the remaining solvent was completely removed. NMR structural characterization: COAPI-6FDA (1:1): 1H NMR (400 MHz, DMSO) δ 10.46 (s, 2H), 8.16 (s, 2H), 8.01 (s, 2H), 7.78 (s, 1H), 7.67 (s, 1H), 7.51 (s, 2H), 7.21 (s, 2H), 7.08(s, 2H). Performance characterization: The method is the same as in Example 1, and the specific results are as follows: COAPI-6FDA (1:1) membrane gas separation test, helium permeability coefficient is 247.9 Barrer, nitrogen permeability coefficient is 10.5 Barrer, oxygen permeability coefficient is 49.1 Barrer, methane permeability coefficient is 8.4 Barrer, carbon dioxide permeability coefficient is 265.4 Barrer, hydrogen permeability coefficient is 308.7 Barrer; The selectivity coefficient of hydrogen / methane is 36.97, the selectivity coefficient of oxygen / nitrogen is 4.67, and the selectivity coefficient of carbon dioxide / methane is 31.79. Example 6 A method for preparing a COPI film (the dianhydride monomer carrying an ether oxygen group is 6FCDA, m:n=1:0, and the diamine part is 6FAP monomer), comprising the following steps: The reaction formula of COPI film (denoted as: COCAPI) is as follows:

[0065] The method is the same as Example 5, except that 6FDA is not added and the amount of 6FCDA added is 2 mmol.

[0066] NMR structural characterization: COCAPI: 1 H NMR (400 MHz, DMSO) δ 10.49 (s, 2H), 8.26 (s, 2H), 8.04 (s,2H), 7.52 (s, 2H), 7.24 (s, 2H), 7.10 (s, 2H). Performance characterization: The method is the same as in Example 1, and the specific results are as follows: COCAPI membrane gas separation test, helium permeability coefficient is 452.9 Barrer, nitrogen permeability coefficient is 19.3 Barrer, oxygen permeability coefficient is 85.7 Barrer, methane permeability coefficient is 20.8 Barrer, carbon dioxide permeability coefficient is 441.6 Barrer, hydrogen permeability coefficient is 563.7 Barrer; The selectivity coefficient of hydrogen / methane is 27.11, the selectivity coefficient of oxygen / nitrogen is 4.45, and the selectivity coefficient of carbon dioxide / methane is 21.23. Comparative Example 2 A method for preparing a copolymer polyimide (COCPI) film (the dianhydride monomer without an ether oxygen group is 6FDA, m:n=0:1, and the diamine part is 6FAP monomer), comprising the following steps: The reaction formula of COPI film (denoted as: CODAPI) is as follows:

[0067] The method is the same as Example 5, except that 6FCDA is not added and the amount of 6FDA added is 2 mmol.

[0068] NMR structural characterization: CODAPI: 1 H NMR (400 MHz, DMSO) δ 10.43 (s, 2H), 8.12 (d, J = 7.3 Hz,2H), 7.94 (s, 2H), 7.73 (s, 2H), 7.49 (s, 2H), 7.19 (s, 2H), 7.08 (s, 2H). Performance characterization: The method is the same as in Example 1, and the specific results are as follows: CODAPI membrane gas separation test, helium permeability coefficient is 191.4 Barrer, nitrogen permeability coefficient is 3.4 Barrer, oxygen permeability coefficient is 21.5 Barrer, methane permeability coefficient is 2.9 Barrer, carbon dioxide permeability coefficient is 109.6 Barrer, hydrogen permeability coefficient is 199.6 Barrer; The selectivity coefficient of hydrogen / methane is 68.23, the selectivity coefficient of oxygen / nitrogen is 6.40, and the selectivity coefficient of carbon dioxide / methane is 37.47.

[0069] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A copolymer polyimide film, characterized in that: Having a structure as shown in Formula I or Formula II:

2. Formula I and Formula II both include a portion of dianhydride monomers with a polymerization degree of m containing ether oxygen groups, and a portion of dianhydride monomers with a polymerization degree of n containing no ether oxygen groups; in, m:n is (1-100):(0-100), and 10 <m+n<1000; X is independently selected from: 、 、 、 、 、 、 ; Ar is independently selected from:

3. The copolymerized polyimide film according to claim 1, characterized in that: m:n is 100:0, 75:25, 50:50, 25:75; Preferably, m:n is 50:

50.

4. The copolymerized polyimide film according to claim 1, characterized in that: X is independently selected from: .

5. The method for preparing a copolymerized polyimide film according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Under a protective atmosphere, add o-hydroxydiamine and solvent to a polymerization tube, mix, add dianhydride monomers carrying ether oxygen groups, dianhydride monomers not carrying ether oxygen groups, and a catalyst, heat to a temperature of 150-180° C. to react, and obtain a viscous reaction solution; S2, treating the viscous reaction solution by solvent precipitation method, drying, and obtaining copolymerized polyimide; S3, dissolving the copolymerized polyimide in a volatile solvent, adding the resulting solution into a culture dish, and evaporating the solvent to obtain a copolymerized polyimide film; wherein, The o-hydroxydiamine has a structure as shown in the following formula: or ; The dianhydride monomer carrying the ether oxygen group has a structure as shown in the following formula: ; X is independently selected from: 、 、 、 、 、 、 ; The dianhydride monomer without an ether oxygen group has a structure as shown in the following formula: ; Ar is independently selected from:

6. The preparation method according to claim 4, characterized in that: In step S1, the ratio of the total amount of dianhydride monomers, o-hydroxydiamine, and catalyst is 2 mmol: 2 mmol: (0.1-2) mL; wherein the total amount of dianhydride monomers is the total molar number of dianhydride monomers carrying ether oxygen groups and dianhydride monomers not carrying ether oxygen groups.

7. The preparation method according to claim 4, characterized in that: In step S1, the catalyst is selected from a basic catalyst and an acidic catalyst; Preferably, the alkaline catalyst comprises at least one of isoquinoline and triethylamine; Preferably, the acidic catalyst includes at least one of benzoic acid and acetic anhydride.

8. The preparation method according to claim 4, characterized in that: In step S1, the solvent includes at least one of m-cresol, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, 1,4-dioxane, and chloroform; In step S3, the volatile solvent includes at least one of tetrahydrofuran, 1,4-dioxane, chloroform and dichloromethane.

9. The preparation method according to claim 4, characterized in that: In step S2, the viscous reaction liquid is treated by a solvent precipitation method. Specifically, the obtained viscous reaction liquid is poured into a mixed solution of ethanol and water, and the mixture is allowed to stand for precipitation to precipitate; Preferably, in the mixed solution of ethanol and water, the volume ratio of ethanol to water is 1:1; In step S2, the drying is specifically performed at 80-120° C. for 1-2 days. The drying step is performed in a vacuum oven.

10. Use of the copolymerized polyimide film according to any one of claims 1 to 3 or the copolymerized polyimide film prepared by the preparation method according to any one of claims 4 to 8 in gas separation.

11. The use according to claim 9, characterized in that: The applications include: using copolymerized polyimide film to separate H2 from H2 / N2 mixed gas, to separate O2 from O2 / N2 mixed gas, to separate CO2 from CO2 / CH4 mixed gas, or to separate at least one of H2 from H2 / CH4 mixed gas or CO2 from CO2 / N2 mixed gas.